Challenges and Benefits of the Semantic Web and the Semantic Grid for E-learning - Bui Minh Tu Diem (Journal of Technical Education Science, 2007)
The complexity of e-learning arises from requirements for dynamicity, interoperability, and semantics handling. Bringing semantics to learning content and services is to provide distributed information with well-defined meaning which is understandable for a wide diversity of parties. This paper explores the need for making the semantics explicit and machine-accessible and outlines the current state of the e-learning technologies specifically the Semantic Web and the Semantic Grid. The aim of this paper is to highlight what such learning technologies bring to e-learning.